Giannozzo Manetti The Life of a Florentine Humanist - Marsh, David 1950- (I Tatti Studies in Italian Renaissance History, 2019)
Giannozzo Manetti was one of the most remarkable figures of the Italian Renaissance, though today his works are unfamiliar in English. In this authoritative biography, the first ever in English, David Marsh guides readers through the vast range of Manetti's writings, which epitomized the new humanist scholarship of the quattrocento